Effect of Guduchi Triphala Kwatha with Lohabhasma as Prakshepa Churna in the Management of Obesity - Neethu Divakaran; Arun Pratap; Lekshmi R; Shan Sasidharan (AYUSHDHARA, 2024)
Obesity a complex metabolic disorder, involves the excessive accumulation of adipose tissue and it is recognised as a major global health challenge. Preclinical study conducted on obesity provides valuable insights into the revalidation of the treatment approach of Sthoulya. Methods: In this study the efficacy of Guduchi Triphala Kwatha added with Lohabhasma, as Prakshepa Churna evaluated in High fat diet (HFD) fed, obese Wistar albino rats. A Control group containing 6 rats were administered with distilled water (9.86ml/kg), another group received standard drug Orlistat (30mg/kg) and the trial group was given Kwatha (9.86ml/kg) added with Lohabhasma (25.65mg/kg). High fat diet was continued throughout the study period. All the drugs were administered orally once a day for 30 days. At the end of the experimental period various physical, biochemical and histopathological observations were made. Results: Data of in-vivo studies revealed that significant reduction in body weight, body mass index (BMI), waist circumference (WC), upon trial drug treatment. Elevated levels of, insulin, leptin, lipid profile, liver function, kidney function and antioxidant status were also showed significant results. Milder changes were observed in histopathological examination of Liver, Kidney and Adipose tissue even though HFD was continuing throughout the study period. Conclusion: The trial drug showed significant result in the assessment parameters after treatment.